Efficient File Replication in Large Wireless Networks with Dynamic Popularity - Gitzenis, Savvas; Toumpis, Stavros; Tassiulas, Leandros (EAI Endorsed Transactions on Cloud Systems, 2014)
We investigate the problem of replication in large wireless networks that employ caching in the case of a single file whose popularity varies with time. As opposed to the case of static popularity, in this case for the network resources to be efficiently allocated the replication should vary with time. In this study, we first outline the low-level operations of wireless networks with caching, which involve decisions of combinatorial complexity, such as about the contents of all network caches. To overcome this complexity, we approximate the network optimization with a formulation based on the frequency of file replication across the network - a high-level perspective, amenable to mathematical analysis. We present a solution that is based on looking ahead into the future and has a simple graphical representation.
Keywords: dynamic content popularity; large wireless networks; caching; multihop; replication